PENYEBAB KORUPSI DALAM PERSPEKTIF TEORITIS : FAKTOR INTERNAL DAN EKSTERNAL DIKALANG MASYARAKAT - Viola Putri Feriska; Aulia Rizky; Putri Handayani; Dewi Aulia Sari; Rangga Putra Andika (Jurnal Riset Multidisiplin Edukasi, 2025)
Corruption is a complex social and legal issue that has become systemically entrenched in various levels of society. From a theoretical perspective, the causes of corruption can be understood through two main aspects: internal and external factors. Internal factors relate to an individual's character and psychological state, such as low integrity, weak moral awareness, and excessive materialistic orientation. Conversely, external factors relate to structural and cultural aspects of society, such as weak law enforcement, bureaucratic intransigence, and a social culture that tends to tolerate corrupt practices. This article seeks to examine these two factors in depth to provide a comprehensive theoretical foundation for strengthening efforts to prevent and eradicate corruption in Indonesia.